2014
DOI: 10.1021/ic500766t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of VIVO Complexes of Picolinate and Pyrazine Derivatives. Behavior in the Solid State and Aqueous Solution and Biotransformation in the Presence of Blood Plasma Proteins

Abstract: Oxidovanadium(IV) complexes with 5-cyanopyridine-2-carboxylic acid (HpicCN), 3,5-difluoropyridine-2-carboxylic acid (HpicFF), 3-hydroxypyridine-2-carboxylic acid (H2hypic), and pyrazine-2-carboxylic acid (Hprz) have been synthesized and characterized in the solid state and aqueous solution through elemental analysis, IR and EPR spectroscopy, potentiometric titrations, and DFT simulations. The crystal structures of the complexes (OC-6-23)-[VO(picCN)2(H2O)]·2H2O (1·2H2O), (OC-6-24)-[VO(picCN)2(H2O)]·4H2O (2·4H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 110 publications
0
34
0
Order By: Relevance
“…The chemical form with which a vanadium compound reaches the target organs affects the uptake by the cells, which can take place through passive diffusion or be mediated by transport proteins. It was shown that the geometry at the physiological pH of a pharmacologically active VOL 2 compound, where L is a bidentate ligand, can influence the interaction with the proteins, such as transferrin (hTf), albumin (HSA), immunoglobulin G (IgG) or hemoglobin (Hb) [39]: when it is cis-octahedral (cis-VOL 2 (H 2 O)), the equatorial water molecule can be replaced by an accessible His-N to form a species with stoichiometry cis-VOL 2 (Protein), whereas when it is square pyramidal (VOL 2 ) no interaction is expected [37,38,[40][41][42][43][44][45][46][47][48][49][50] …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The chemical form with which a vanadium compound reaches the target organs affects the uptake by the cells, which can take place through passive diffusion or be mediated by transport proteins. It was shown that the geometry at the physiological pH of a pharmacologically active VOL 2 compound, where L is a bidentate ligand, can influence the interaction with the proteins, such as transferrin (hTf), albumin (HSA), immunoglobulin G (IgG) or hemoglobin (Hb) [39]: when it is cis-octahedral (cis-VOL 2 (H 2 O)), the equatorial water molecule can be replaced by an accessible His-N to form a species with stoichiometry cis-VOL 2 (Protein), whereas when it is square pyramidal (VOL 2 ) no interaction is expected [37,38,[40][41][42][43][44][45][46][47][48][49][50] …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Oxidovanadium(IV), V IV O, compounds 1 and 2 were synthesized from VOSO 4 Á5H 2 O and HpicFF or H 2 hypic as described previously. 18 Dioxidovanadate(V) and V V O 2 , compounds were prepared from ammonium metavanadate and the corresponding picolinic acid analogues, HpicFF (3) or H 2 hypic (4), in a 1 : 2 ratio in methanol or water/methanol, respectively. Zinc(II) bis(3,5-difluoropicolinato) and bis(3-hydroxypicolinato) complexes were prepared in two steps.…”
Section: Synthesis and Ir Spectroscopymentioning
confidence: 99%
“…25 Lately, we have been studying V IV O compounds with picolinic acid and pyrazine derivatives concerning their structures and interactions with serum proteins. 18 For compounds 1 and 2 three isomers were observed by EPR in an organic solvent or in aqueous solution. The H 2 hypic was found to be the strongest ligand and the HpicFF the weakest one and thus different biotransformations at physiological pH in the presence of apo-transferrin and human serum albumin were observed.…”
Section: Structural Comparisonmentioning
confidence: 99%
See 2 more Smart Citations